Standard Operating Procedures of antenatal care and its relation with pregnant women's satisfaction during pregnancy examination: Results of a survey at Gamping I Public Health Center, Yogyakarta, Indonesia - Hilma Triana; Sulistyaningsih Sulistyaningsih; Jumpanata Jumpanata; Yogi Yamani (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2023)
Background: The achievement parameter for maternal health services program is the access of pregnant health services, as indicated by measuring the coverage of antenatal care services. In Indonesia, examination of pregnant women according to antenatal standards is regulated by Ministry of Health Indonesia Number 21 of 2021, where pregnancy checks must fulfill the standard 10 T criteria. Aims: This study aimed to identify the Standard Operating Procedures of antenatal care in Gamping I Public Health Center, Yogyakarta, Indonesia, and determine its relation with pregnant women's satisfaction during pregnancy examination. Methods: Of 70 TM III pregnant women, who routinely visit for antenatal care service at the Public Health Center Gamping I, a total of 40 pregnant women were selected using consecutive sampling with 10% margin of error. A set of questionnaires was distributed to the respondents to asses: (1) The implementation of the antenatal care service standard (20 questions, and weighted using a dichotomy scale) and (2) The pregnant women satisfaction (22 questions, and weighted using the Likert scale. The data obtained from respondents were then tabulated and processed using Microsoft Office Excel 2010 and then analyzed using the SPSS Statistics 16.0 program (Pearson Product Moment formula with an error rate of 5%). Results: There are 10 pregnancy tests (10T) received by the pregnant women at the health center including the measurement of Height, Weight, Blood pressure, upper arm circumference, Uterine fundus height, Presentation & Fetal heart rate, Provision of 90 Fe Tablets, Laboratory examinations, Case handling, TT Immunization Screening, and Counseling & mental health assessment. According to the findings of the research conducted by the researchers, antenatal examinations were not carried out in a comprehensive and thorough manner in instances. This article provides the women satisfaction to the antennal care on different dimensions of satisfaction including Physical Proof, Reliability, Responsiveness, Guarantee, and Empathy. Even though the analysis shows that the respondents was satisfied with the antennal care services; however, the relation is not statistically significant (p-value of 0.652). Conclusion : One's satisfaction is very difficult to measure and someone's satisfaction is different from the satisfaction of someone else. According to the findings of the study, every time a midwife performed an antenatal checkup, she had never provided complete 10T-based antenatal care. In addition, this research has been carried out through direct observation of prenatal care, where pregnant women and midwives' perceptions of antenatal care examinations do not differ.